Characteristics of Restructured Mackerel Meat Jerky (Study of Mackerel Meat Proportion: Young Jackfruit) and Addition of Na-Alginate - Citra Melia Agustin; Ratna Yulistiani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Restructured jerky is a processed meat product created by binding small meat pieces with binders such as sodium alginate (Na-Alginate). This study aimed to determine the optimal combination of mackerel and young jackfruit proportions with Na-Alginate to produce high-quality restructured jerky. A completely randomized design (CRD) with a two-factor factorial arrangement and two replications was employed. Factor I varied the proportions of mackerel to young jackfruit (65:35, 50:50, 35:65), and Factor II varied the Na-Alginate addition (0.25%, 0.50%, 0.75%). Data were analyzed using analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) for post-hoc comparisons. The optimal result was achieved with a mackerel to young jackfruit ratio of 65:35 and 0.50% Na-Alginate, producing restructured jerky with the following characteristics: 8.02% water content, 0.44% ash content, 2.32% crude fiber, 42.20% yield, 0.47% water activity (aw), 22.84% protein content, 2.98% fat content, and hedonic organoleptic scores for color (3.56, like), aroma (3.00, like), taste (3.16, like), and texture (3.16, like).